Penerapan Model Pembelajaran Teams Games Tournament (TGT) Terhadap Hasil Belajar Peserta Didik Kelas XI Mia SMA Negeri 4 Pulau Morotai Kecamatan Morotai Utara - M. Iksan B. Aly; Ningsi Kamoro (Peneliti.net, 2022)
Education is an important means to improve the quality of human resources (HR) in ensuring the continuity of development developed by a nation. The potentials of students need to be developed in education to understand learning concepts so that education can run well. Education goes well if the components in it can run well too. Learning outcomes are experiences that have been obtained by students after receiving learning. In accordance with the statement (Febryananda 2019) that learning outcomes are mastery that has been obtained by someone or after students absorb the learning experience. Meanwhile, according to (Rusman 2014), learning outcomes are a number of experiences gained by students covering the cognitive, effective, and psychomotor domains. Learning is not only mastering the concepts of learning theory, but also mastering habits, perceptions, pleasures, interests, talents, social adjustments, types of skills, ideals, desires and hopes. This study aims to improve the learning outcomes of students in class XI MIA SMA Negeri 4 Morotai Island, North Morotai District. This research is a classroom action research (CAR). The research was carried out in two cycles. The subjects of this study were students of class XI MIA SMA Negeri 4 Morotai Island, North Morotai District, totaling 23 students. The technique of data collection is cycle test observation. Based on the results of classroom action research (CAR) and discussions that have been carried out for two cycles, it can be concluded that the use of the Teams Games Tournament (TGT) learning model can improve the learning outcomes of students in class XI MIA SMA Negeri 4 Morotai Island in the 2021/learning year. 2022. The mastery of student learning outcomes in the first cycle was 65% and in the second cycle there was an increase of 76.7%.